Development and testing of a scale for assessing the protective factors of teachers' resilience - Daniilidou, Athena; Platsidou, Maria (Psychology: the Journal of the Hellenic Psychological Society, 2022)
Resilience is an important resource for teachers' quality of life and functional work. Yet, there are very few scales for measuring it addressed specifically to teachers; in fact, those existing do not include many of the important resilience protective factors. To fill this gap, based on relevant qualitative data collected earlier, this study aimed to design and evaluate a more comprehensive scale for measuring the personal and environmental protective factors of teachers' resilience. The sample consisted of 407 primary school teachers. The Multidimensional Teachers’ Resilience Scale (Mansfield & Wosnitza, 2015) and the Teachers’ Resilience Scale (Daniilidou & Platsidou, 2018) were used to test the convergent validity of the new scale. The Maslach Burnout Inventory (Maslach & Jackson, 1986) and the Teachers’ Sense of Efficacy Scale (Tschannen-Moran & Woolfolk Hoy, 2001) were used to assess the discriminant validity of the new scale. Through a series of factor analyses and item response analyses using a polytomous graded model, the final version of the Teachers’ Protective Factors of Resilience Scale (TPFRS) emerged. It includes 29 items which assess six protective factors of teachers’ resilience: Values ​​and beliefs, Emotional and behavioral competence, Physical well-being, In-school relationships, Out-of-school relationships and the Legislative framework. The good psychometric properties of the TPFRS as well as its distinctive and convergent validity showed that it can be safely used in future research on teachers' resilience.